Zolmitriptan inhibits neurogenic inflammation and pain during electrical stimulation in human skin. (13th November 2014) - Döring, K.; Best, C.; Birklein, F.; Krämer, H.H.
Abstract Background Triptans are agonists to 5‐HT 1B/D/F receptors, which are present on nociceptive neurons not only within but also beyond the trigeminal system. The aim of this study was to investigate whether zolmitriptan interacts with peptidergic nociceptive afferents in human skin. Methods Twenty participants (13 women, median age: 25; interquartile range: 23–26 years) entered the randomized, double‐blind, cross‐over study. Electrically induced neurogenic flare and pain was assessed after either placebo or zolmitriptan on the ventral thigh. Mechanical pain thresholds were investigated at baseline and after electrical stimulation at the stimulation site. Results The size of the neurogenic flare (F = 10.9; p = 0.002) as well as electrically induced pain were significantly reduced by zolmitriptan (F = 4.46; p = 0.041). Moreover, electrically induced pinprick hyperalgesia was significantly decreased by zolmitriptan compared with placebo (F = 6.243; p = 0.017). Conclusions Triptans may have effects outside of the trigeminal system and reduce electrically evoked neurogenic inflammation and pain in human skin.